IN - VITRO CALLUS INDUCTION IN LEAF EXPLANTS OF TAGETES ERECTA, L - NIKAM S.L.; KHAN S. J. (International Journal of Pharma and Bio Sciences, 2014)
Tagetes erecta is an industrially and commercially important ornamental plant belonging to family Asteraceae. Developing tissue culture technique for Tagetes erecta will permit the application of biotechnology to its culture and potential for exploitatation of phytochemicals. The present work is based on developing protocols for the callus induction in Tagetes erecta from leaf explants. The sterilized explants were inoculated in Murashige and Skoog (MS) media containing various combinations of auxins such as Naphthalene acetic acid (NAA), Indole 3-acetic acid (IAA), Indole 3-butyric acid (IBA), 2,4 Dichlorophenoxyacetic acid (2,4 D) and cytokinins such as Kinetin (KIN) and Benzylaminopurines (BAP). The highest rate of callus induction for Tagetes leaf was achieved on media supplemented with 2, 4 D (2 mg/L ) and BAP (5mg/L) with compact, fast growing, pale yellow coloured callus. Leaf explans were grown with IAA, IBA, NAA and KIN at different concentrations to evaluate tissue responses such as production of proembryo and roots in the explant.